(untitled) (Homoeopathy for All, 2025)
Accurate observation is the cornerstone of homoeopathic practice. In homoeopathy the selection of remedy mainly depends upon the observation. For fine prescription there is the need of trained unprejudiced observer who select the remedy on the basis of keen observation. Samuel Hahnemann emphasized that a physician must train the senses to perceive, record, and interpret even the most delicate signs of disease and medicinal action. Dr. Stuart Close further refined this by outlining how bedside observations—mental, physical, and environmental—become essential for individualizing a case. This article explores the philosophy of observation, its clinical application, and its representation in standard repertories such as Kent and Murphy. The aim is to highlight how observation bridges the patient’s unique expression of illness with the choice of the similimum